Comparison of aircraft engine performance and emission analysis using alternative fuels - Azami, Muhammad Hanafi; Savill, Mark; Li, Yi-Guang (Inderscience Enterprises, 2017)
Following the successful flights of many commercial aircraft running with alternative fuels, the present study focuses on aircraft engine performance and emission analysis. The analysis of aircraft engine performance (thrust, fuel flow and specific fuel consumption) for different blended mixing ratio percentages of biofuels (Camelina and Jatropha) with Jet-A, at different flight conditions using in-house computer software codes, PYTHIA & TURBOMATCH. Emission analysis utilised HEPHAESTUS in-house software to predict nitrous oxides and carbon monoxide emission at various flight conditions. A model three-shaft high-bypass-ratio engine, similar to the RB211-524, was used. Blended fuels exhibited a slight improvement in engine performance at higher mixing ratio percentages; with Jatropha biofuel surpassing Camelina biofuel in terms of all considered performance indexes. Nitrous oxides can be reduced using pure Jatropha biofuel as compared to kerosene fuel for every flight condition. However, for carbon monoxide emission strongly depends on the combustor inlet conditions and flight phases.